Discrete Model of Wave Propagation in a Nonprismatic Bar with Rigid Unloading Characteristics - Z. Szcześniak (Engineering Transactions)
A discrete model is proposed for the propagation of waves in a nonprismatic bar made from a material whose unloading characteristic is rigid. Arbitrary time-dependent applied load is considered. In such a situation the modelling of wave propagation must allow in each cross-section for multiple effects of its alternating rigid and activated behaviour. These effects are nonlinear and thus it is very difficult to approach them analytically. An algorithm for numerical solutions is proposed and errors of the results are discussed. Effectiveness and applicability of the model are illustrated by means of numerical examples.